Quantizing single-molecule surface-enhanced Raman scattering with DNA origami metamolecules - Fang, Weina; Duan, Xiaoyang; Liu, Na (Science advances, 2019)
Tailored metal nanoclusters have been actively developed to manipulate light at the subwavelength scale for nanophotonic applications. Nevertheless, precise arrangement of molecules in a hot spot with fixed numbers and positions remains challenging. Here, we show that DNA origami metamolecules with Fano resonances (DMFR) can precisely localize single dye molecules and produce quantified surface-enhanced Raman scattering (SERS) responses. To enable tailored plasmonic permutations, we develop a general and programmable method for anchoring a set of large gold nanoparticles (L-AuNPs) on prescribed n-tuple docking sites of super-origami DNA frameworks. A tetrameric nanocluster with four spatially organized 80-nm L-AuNPs exhibits peak-and-dip Fano characteristics. The drastic enhancement at the wavelength of the Fano minimum allows the collection of prominent SERS spectrum for even a single dye molecule. We expect that DMFR provides physical insights into single-molecule SERS and opens new opportunities for developing plasmonic nanodevices for ultrasensitive sensing, nanocircuits, and nanophotonic lasers. - Plasmonic nanostructures supporting strong spatially confined field enhancement are developed to probe single-molecule SERS. - Plasmonic nanostructures supporting strong spatially confined field enhancement are developed to probe single-molecule SERS.